FINANCING IN THE PERSPECTIVE OF SHARIAH BANKING - Mujahidin Mujahidin (JURNAL ILMIAH EDUNOMIKA, 2022)
The purpose of this study is to see how financing in the Islamic economy is managed through Islamic banking. Islamic financing, also known as Sharia-compliant financing, is a system of financial practices that adhere to the principles of Islamic law (Sharia). Sharia prohibits the collection and payment of interest (riba) and requires that all financial transactions be conducted in a manner that is ethical and socially responsible. Research method is Literature review is a systematic, explicit and reproducible method for identifying, evaluating and synthesizing works of research results and ideas that have been produced by researchers and practitioners. Literature review aims to make an analysis and synthesis of existing knowledge related to the topic to be researched to find empty space for research to be carried out. Result of this research There are various types of Islamic banking financing instruments available, each with its own features and benefits. Some of the most commonly used instruments include: Mudarabah, Musharakah, Murabah, Ijarah, Sukuk